Augmentation of systemic resistance and secondary metabolites by chitinolytic microbes in Withania somnifera against Meloidogyne incognita. Issue 12 (1st December 2016) - Gupta, Rupali; Singh, Akanksha; Srivastava, Madhumita; Gupta, M. M.; Pandey, Rakesh
ABSTRACT: Ashwagandha ( Withania somnifera L. Dunal), a therapeutically imperative herb is known for its useful steroidal lactones (withanolide and withaferin) and acyl steryl glycosides. The plant is a highly susceptible host for the plant parasitic nematode, Meloidogyne incognita . Selected chitinolytic microbes, namely Cellulosimicrobium cellulans MTN13, Flavobacterium johnsoniae MTN 20, Chitiniphilus sp. MTN22 and Streptomyces sp. MTN14, alone and in combination for M. incognita management and enhancement of secondary metabolites in W. somnifera cv. Poshita were evaluated. A significant enhancement in biomass yield (1.9-fold) and disease diminution (2.7-fold) was found in the dual microbial treatment Streptomyces sp. and Chitiniphilus sp. with respect to the untreated inoculated control plants. A significant augmentation (2.7- and 2.0-fold, respectively) in withanolide A and withaferin A was also found in the same treatment. The studies revealed increment of defence variables 1.1- to 1.3-fold and 1.6- to 2.1-fold in single- and dual-microbe treatments, respectively, than the untreated inoculated plants. The stimulation of the phenylpropanoid pathway and phenolics accumulation was the maximum at 5 days post inoculation (dpi), whereas antioxidant enzymes activities were the highest at 7 dpi. The results thus highlight a possible new function of chitinolytic microbes alone and in combinations that can effectively manage M. incognita -induced stress along with enhanced active molecules of W. somnifera .